Polyacrylonitrile-itaconic acid fibrofelt reinforced carbon aerogel composite material as well as preparation method and application thereof

By introducing polyacrylonitrile-itaconic acid fiber felt reinforcement into carbon aerogel materials, the problems of low strength, high brittleness and large volume shrinkage in the preparation process are solved, and composite materials with excellent mechanical properties and low thermal conductivity are prepared, which are suitable for aerospace heat insulation and other fields.

CN119569475AActive Publication Date: 2025-03-07DONGHUA UNIV +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510137977.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The application of existing carbon aerogel materials in the field of aerospace heat insulation is limited by their shortcomings such as low strength, high brittleness, and large volume shrinkage in the preparation process, and their preparation process is complex and their cost is high.

Method used

Polyacrylonitrile-itaconic acid fiber felt is used as the reinforcement to prepare composite materials through impregnation, curing, carbonization and other processes to improve the network strength of carbon aerogels, reduce volume shrinkage, and reduce production costs.

Benefits of technology

The prepared polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material has high porosity, low density, low thermal conductivity and excellent mechanical properties, and is suitable for thermal insulation, adsorption and electromagnetic shielding applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569475A_ABST
    Figure CN119569475A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aerogel composite materials, and provides a polyacrylonitrile-itaconic acid fibrofelt reinforced carbon aerogel composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: impregnating polyacrylonitrile-itaconic acid fiber felt in a pre-polymerization solution composed of a phenol monomer, an aldehyde monomer, an alcohol solvent and an acid catalyst under normal pressure, then carrying out a sol-gel reaction, and sequentially carrying out normal-pressure drying and a carbonization reaction on the obtained composite material precursor, the acidic catalyst comprises one or more of hydrochloric acid, salicylic acid, m-hydroxybenzoic acid and gallic acid. According to the invention, the polyacrylonitrile-itaconic acid fiber felt is used as a reinforcement body, and is impregnated, cured and carbonized in the pre-polymerization solution containing the acid catalyst, so that the prepared carbon aerogel composite material has the advantages of high porosity, low density, high specific surface area, low thermal conductivity and excellent mechanical property and thermal insulation property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel composite materials, and in particular to a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material and a preparation method and application thereof. Background Art

[0002] The development of new high-speed aerospace vehicles urgently requires high-performance thermal insulation materials that are resistant to ultra-high temperatures, have low thermal conductivity, and have high strength. Carbon aerogel is a three-dimensional network structure nanoporous material formed by interconnected carbon nanoparticles. It has the advantages of low density, ultra-high temperature resistance, and low radiative thermal conductivity, but it has disadvantages such as low strength, high brittleness, and large inherent volume shrinkage during the preparation process, which limits its application in the field of aerospace thermal insulation. Therefore, the development of new high-performance thermal insulation materials with performance characteristics such as ultra-high temperature resistance, ultra-low thermal conductivity, and sufficient strength has become one of the main research hotspots in the field of thermal insulation materials.

[0003] Researchers are committed to improving the thermal insulation and mechanical comprehensive properties of carbon aerogels. Chinese patent CN115504451A uses a high-temperature hydrothermal method to obtain high specific surface area (1100~1600m 2 / g) of carbon aerogel, wherein alkali metal-sodium carbonate is used as a catalyst, and the Na + It has a corrosive effect on the subsequent high-temperature carbonization equipment, which is not conducive to mass production. In addition, supercritical drying has high requirements for equipment, which increases production costs. Chinese patent CN118954482A uses fiber-reinforced carbon aerogel to obtain fiber-reinforced carbon aerogel composite materials through gelation, aging, drying, solvent replacement, and high-temperature carbonization. The solvent replacement process prolongs the preparation cycle and increases the cost of raw materials. Chinese patent CN118637937B uses an impregnation solution formed by a mixture of phenolic aerogel powder, phenolic resin, and dispersant to impregnate carbon aerogel. After ultrasonic secondary impregnation, gelation, aging and carbonization, a low density (0.26~0.41g / cm 3 ), ablation-resistant thermal insulation carbon aerogel composite materials with general room temperature thermal insulation (0.055~0.068W / m·K), have complex processes, long preparation cycles and high equipment requirements.

[0004] Therefore, the research obtained a preparation method of polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material with good mechanical properties, short preparation cycle and low production cost, which is of great significance to better solve a series of problems such as long preparation cycle, high equipment requirements, poor mechanical properties, high brittleness and high production cost. Summary of the invention

[0005] The purpose of the present invention is to provide a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material and a preparation method and application thereof in order to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, comprising the following steps: 1) Mixing phenol monomer, aldehyde monomer, alcohol solvent and acid catalyst to obtain a prepolymerization solution; 2) impregnating polyacrylonitrile-itaconic acid fiber felt in a prepolymerization solution at normal pressure and then performing a sol-gel reaction to obtain a composite material precursor; 3) drying and carbonizing the composite material precursor in sequence at normal pressure to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material; The acidic catalyst comprises one or more of hydrochloric acid, salicylic acid, m-hydroxybenzoic acid and gallic acid.

[0007] Preferably, in step 1), the molar ratio of the phenolic monomer, the aldehyde monomer, the acidic catalyst and the alcohol solvent is 1:2.0-2.5:3.6-5.0:40-45.

[0008] Preferably, the phenolic monomer comprises one or more of phenol, resorcinol, aminophenol, butylphenol and bisphenol A; the aldehyde monomer comprises one or more of formaldehyde, glutaraldehyde, paraformaldehyde and furfural; the alcohol solvent comprises one or more of anhydrous ethanol, n-propanol, isopropanol and n-butanol.

[0009] Preferably, in step 1), the mixing speed is 300-450 rpm, and the mixing temperature is 30-50°C.

[0010] Preferably, the polyacrylonitrile-itaconic acid fiber felt is prepared by the following steps: acrylonitrile, itaconic acid, an initiator and a solvent are polymerized to obtain an acrylonitrile copolymer, and the acrylonitrile copolymer is sequentially subjected to dry-jet wet spinning and needle punching to obtain the polyacrylonitrile-itaconic acid fiber felt; the mass ratio of acrylonitrile to itaconic acid is 97~99:2.

[0011] Preferably, in step 2), the temperature of the sol-gel reaction is 60-70° C., and the time of the sol-gel reaction is 11-13 h.

[0012] Preferably, in step 3), the temperature of the normal pressure drying is 90-120° C., and the normal pressure drying time is 10-18 hours.

[0013] Preferably, in step 3), the temperature of the carbonization reaction is 800-1400° C., the time of the carbonization reaction is 2 h, and the heating rate from room temperature to the carbonization reaction temperature is 3-5° C. / min; the carbonization reaction is carried out under a nitrogen atmosphere.

[0014] The present invention also provides a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared by the preparation method of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, wherein the density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material is 0.13-0.16 g / cm 3 , the specific surface area is 1662~1942m 2 / g, thermal conductivity at room temperature is 0.017~0.049W / m·K , The compression strength is 2.17~4.03MPa.

[0015] The present invention also provides the application of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, and the application of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material in thermal insulation, adsorption and electromagnetic shielding.

[0016] The beneficial effects of the present invention include the following: 1) The present invention adopts polyacrylonitrile-itaconic acid fiber felt as a reinforcement, and prepares a composite material through processes such as impregnation, curing, and carbonization, so as to functionalize the network of the carbon aerogel, improve the network strength, and reduce the volume shrinkage. The prepared polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material has high porosity, low density, high specific surface area, low thermal conductivity, and excellent mechanical properties and thermal insulation properties.

[0017] 2) The present invention adds alcohol solvents and acidic catalysts during the sol-gel reaction process. Compared with alkaline catalysts, acidic catalysts can shorten the solution-gel reaction time, accelerate the reaction rate, and do not require solvent replacement and supercritical freeze drying. The volume shrinkage is less than 20%, thereby reducing energy consumption. The acidic catalyst has a pore-forming effect, which gives the composite material a high porosity, reduces the volume shrinkage rate of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material during normal pressure drying, increases the specific surface area, and improves production efficiency.

[0018] 3) The present invention can adjust the pore size distribution and porosity of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material by reasonably controlling process parameters such as raw material ratio, sol-gel reaction time, and carbonization temperature.

[0019] 4) The preparation method of the present invention does not require solvent replacement and secondary activation processes, does not require freeze drying, and only requires normal pressure drying. It has low raw material cost, simple process, and strong processability. It provides an effective method for the large-scale production of carbon aerogels and has important practical significance for the development of new aerospace vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a nitrogen adsorption test diagram of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1; Figure 2 This is a SEM image of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1; Figure 3 This is an X-ray diffraction spectrum of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1; Figure 4 This is a Raman spectrum of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1; Figure 5 This is a compressive stress-strain curve of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1. DETAILED DESCRIPTION

[0021] The present invention provides a method for preparing a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, comprising the following steps: 1) Mixing phenol monomer, aldehyde monomer, alcohol solvent and acid catalyst to obtain a prepolymerization solution; 2) impregnating polyacrylonitrile-itaconic acid fiber felt in a prepolymerization solution at normal pressure and then performing a sol-gel reaction to obtain a composite material precursor; 3) drying and carbonizing the composite material precursor in sequence at normal pressure to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material; The acidic catalyst comprises one or more of hydrochloric acid, salicylic acid, m-hydroxybenzoic acid and gallic acid.

[0022] In the present invention, the molar ratio of the phenolic monomer, aldehyde monomer, acidic catalyst and alcohol solvent in step 1) is preferably 1:2.0-2.5:3.6-5.0:40-45, more preferably 1:2.2-2.4:4.0-4.8:41-44, and more preferably 1:2.3:4.3-4.5:42-43.

[0023] In the present invention, the phenolic monomer preferably includes one or more of phenol, resorcinol, aminophenol, butylphenol, and bisphenol A; the aldehyde monomer preferably includes one or more of formaldehyde, glutaraldehyde, paraformaldehyde and furfural; the alcohol solvent preferably includes one or more of anhydrous ethanol, n-propanol, isopropanol and n-butanol.

[0024] In the present invention, the mixing speed in step 1) is preferably 300-450 rpm, more preferably 320-400 rpm, more preferably 350-360 rpm; the mixing temperature is preferably 30-50°C, more preferably 35-45°C, more preferably 40°C.

[0025] In the present invention, the mixing in step 1) is preferably a mixture of phenolic monomer, alcohol solvent and acidic catalyst to obtain a mixed solution, and the aldehyde monomer is further mixed with the mixed solution to obtain a prepolymer solution; the mixing time of the phenolic monomer, alcohol solvent and acidic catalyst is preferably 10 to 40 minutes, more preferably 20 to 30 minutes, and more preferably 25 minutes; the mixing time of the aldehyde monomer and the mixed solution is preferably 10 minutes.

[0026] In the present invention, the polyacrylonitrile-itaconic acid fiber felt is preferably prepared by the following steps: acrylonitrile, itaconic acid, an initiator and a solvent are mixed under a nitrogen atmosphere, and the mixed solution is subjected to a polymerization reaction to obtain an acrylonitrile copolymer; the acrylonitrile copolymer is filtered and degassed in sequence to obtain a spinning solution; the spinning solution is subjected to dry-jet wet spinning, drawing, oiling, drying and densification, hot steam drawing, and heat setting in sequence to obtain polyacrylonitrile-itaconic acid fibers, and the polyacrylonitrile-itaconic acid fiber felt is obtained by needle punching.

[0027] In the present invention, the mass ratio of acrylonitrile to itaconic acid is preferably 97-99:2, and more preferably 98:2; in the mixed solution, the total mass concentration of acrylonitrile and itaconic acid is preferably 23-28%, more preferably 24-26%, and more preferably 25%, and the mass concentration of the initiator is preferably 0.7-0.9%, and more preferably 0.8%; the initiator is preferably azobisisobutyronitrile.

[0028] In the present invention, the polymerization reaction temperature is preferably 50 to 70° C., more preferably 55 to 65° C., and more preferably 60° C., and the polymerization reaction time is preferably 11 to 13 h, and more preferably 12 h.

[0029] In the present invention, itaconic acid is used as the second comonomer.

[0030] In the present invention, the atmospheric pressure impregnation in step 2) is carried out at room temperature, and the atmospheric pressure impregnation time is preferably 8 to 12 minutes, more preferably 9 to 11 minutes, and more preferably 10 minutes.

[0031] In the present invention, the temperature of the sol-gel reaction in step 2) is preferably 60-70°C, more preferably 62-67°C, more preferably 65°C, and the time of the sol-gel reaction is preferably 11-13h, more preferably 12h.

[0032] In the present invention, the sol-gel reaction is preferably carried out in a closed mold.

[0033] In the present invention, the temperature of the atmospheric pressure drying in step 3) is preferably 90-120°C, more preferably 95-110°C, more preferably 100-105°C, and the atmospheric pressure drying time is preferably 10-18h, more preferably 11-15h, more preferably 12h.

[0034] In the present invention, the temperature of the carbonization reaction in step 3) is preferably 800-1400°C, more preferably 1000-1300°C, more preferably 1100-1200°C, and the carbonization reaction time is preferably 2h; the heating rate from room temperature to the carbonization reaction temperature is preferably 3-5°C / min, more preferably 3.5-4.5°C / min, more preferably 4°C / min; the carbonization reaction is preferably carried out under a nitrogen atmosphere.

[0035] The present invention also provides a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared by the preparation method of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0036] In the present invention, the density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material is 0.13-0.16 g / cm 3 , the specific surface area is 1662~1942m 2 / g, room temperature thermal conductivity is 0.017~ 0.049W / m·K, and compressive strength is 2.17~4.03MPa.

[0037] The present invention also provides the application of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, and the application of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material in thermal insulation, adsorption and electromagnetic shielding.

[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0039] In the embodiment, the preparation process of polyacrylonitrile-itaconic acid fiber felt is as follows: acrylonitrile, itaconic acid, an initiator (azobisisobutyronitrile) and dimethyl sulfoxide are mixed, and the mixed solution is polymerized at 60°C for 12 hours to obtain an acrylonitrile copolymer, wherein the total mass concentration of acrylonitrile and itaconic acid in the mixed solution is 25%, the mass concentration of the initiator is 0.8%, and the mass ratio of acrylonitrile to itaconic acid is 98:2; the acrylonitrile copolymer is filtered and degassed in sequence to obtain a spinning solution; the spinning solution is subjected to dry-jet wet spinning, drawing, oiling, drying and densification, hot steam drawing, and heat setting in sequence to obtain polyacrylonitrile-itaconic acid fiber, which is needle-punched to obtain polyacrylonitrile-itaconic acid fiber felt; the polyacrylonitrile-itaconic acid fiber felt is washed with deionized water and placed in an oven for drying at 60°C for 12 hours.

[0040] Example 1 Phenol, anhydrous ethanol and hydrochloric acid (hydrogen chloride concentration is 1 mol / L) are stirred at 30°C and 300 rpm for 10 minutes to obtain a uniform mixed solution; the mixed solution and formaldehyde are mixed and stirred at 30°C and 300 rpm for 10 minutes to obtain a uniform prepolymer solution; wherein the molar ratio of hydrogen chloride to anhydrous ethanol in phenol, formaldehyde and hydrochloric acid is 1:2.0:3.6:43.

[0041] The dried polyacrylonitrile-itaconic acid fiber felt was uniformly immersed in the prepolymerization solution at normal pressure and room temperature for 10 minutes, and then a sol-gel reaction was carried out in a sealed crystallization dish (diameter 90 mm) at 60°C for 12 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material precursor.

[0042] The composite material precursor was dried at 100°C under normal pressure for 12 hours to obtain a dry gel; the dry gel was carbonized in a high-purity nitrogen atmosphere, the temperature was increased from room temperature to 800°C at a rate of 5°C / min, and the dry gel was carbonized at 800°C for 2 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0043] The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is 0.13 g / cm 3 , with a specific surface area of ​​1942m 2 / g, the thermal conductivity at room temperature is 0.017W / m·K, the thermal conductivity at 1500℃ is 0.05W / m·K, the compressive strength is 4.03MPa, and the compression modulus is 6.72MPa.

[0044] Example 2 The toluene diphenol, n-propanol and salicylic acid are stirred at 40°C and 350 rpm for 30 minutes to obtain a uniform mixed solution; the mixed solution and glutaraldehyde are mixed and stirred at 40°C and 350 rpm for 10 minutes to obtain a uniform prepolymer solution; wherein the molar ratio of toluene diphenol, glutaraldehyde, salicylic acid and n-propanol is 1:2.4:4.3:42.

[0045] The dried polyacrylonitrile-itaconic acid fiber felt was uniformly immersed in the prepolymerization solution at normal pressure and room temperature for 10 minutes, and then a sol-gel reaction was carried out in a sealed crystallization dish (diameter 90 mm) at 70°C for 11 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material precursor.

[0046] The composite material precursor was dried at 110°C under normal pressure for 11 hours to obtain a dry gel; the dry gel was carbonized in a high-purity nitrogen atmosphere, the temperature was increased from room temperature to 1000°C at a rate of 3°C / min, and the dry gel was carbonized at 1000°C for 2 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0047] The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 2 is 0.15 g / cm 3 , with a specific surface area of ​​1777m 2 / g, room temperature thermal conductivity is 0.022W / m·K, compressive strength is 2.17MPa, and compression modulus is 3.62MPa.

[0048] Example 3 Bisphenol A, n-butanol and m-hydroxybenzoic acid are stirred at 50°C and 300 rpm for 40 minutes to obtain a uniform mixed solution; the mixed solution and furfural are mixed and stirred at 50°C and 400 rpm for 10 minutes to obtain a uniform prepolymer solution; wherein the molar ratio of bisphenol A, furfural, m-hydroxybenzoic acid and n-butanol is 1:2.5:5:40.

[0049] The dried polyacrylonitrile-itaconic acid fiber felt was uniformly immersed in the prepolymerization solution at normal pressure and room temperature for 10 minutes, and then a sol-gel reaction was carried out in a sealed crystallization dish (diameter 90 mm) at 70°C for 11 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material precursor.

[0050] The composite material precursor was dried at 90°C under normal pressure for 18 hours to obtain a dry gel; the dry gel was carbonized in a high-purity nitrogen atmosphere, the temperature was increased from room temperature to 1200°C at a rate of 5°C / min, and the dry gel was carbonized at 1200°C for 2 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0051] The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 3 is 0.14 g / cm 3 , with a specific surface area of ​​1801m 2 / g, room temperature thermal conductivity is 0.024W / m·K, compressive strength is 3MPa, and compression modulus is 5MPa.

[0052] Example 4 Butylphenol, isopropanol and gallic acid are stirred at 40°C and 450 rpm for 25 minutes to obtain a uniform mixed solution; the mixed solution and polyformaldehyde are mixed and stirred at 40°C and 400 rpm for 10 minutes to obtain a uniform prepolymerization solution; wherein the molar ratio of butylphenol, polyformaldehyde, gallic acid and isopropanol is 1:2.2:4.5:45.

[0053] The dried polyacrylonitrile-itaconic acid fiber felt was uniformly immersed in the prepolymerization solution at normal pressure and room temperature for 10 minutes, and then a sol-gel reaction was carried out in a sealed crystallization dish (diameter 90 mm) at 65°C for 13 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material precursor.

[0054] The composite material precursor was dried at 120°C under normal pressure for 10 hours to obtain a dry gel; the dry gel was carbonized in a high-purity nitrogen atmosphere, the temperature was increased from room temperature to 1400°C at a rate of 5°C / min, and the dry gel was carbonized at 1400°C for 2 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0055] The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 4 is 0.16 g / cm 3 , with a specific surface area of ​​1705m 2 / g, room temperature thermal conductivity is 0.039W / m·K, compressive strength is 2.69MPa, and compression modulus is 4.49MPa.

[0056] Example 5 2-Aminophenol, n-butanol and m-hydroxybenzoic acid are stirred at 40°C and 350 rpm for 30 minutes to obtain a uniform mixed solution; the mixed solution and formaldehyde are mixed and stirred at 40°C and 350 rpm for 10 minutes to obtain a uniform prepolymer solution; wherein the molar ratio of 2-aminophenol, formaldehyde, m-hydroxybenzoic acid and n-butanol is 1:2.4:4.5:42.

[0057] The dried polyacrylonitrile-itaconic acid fiber felt was uniformly immersed in the prepolymerization solution at normal pressure and room temperature for 10 minutes, and then a sol-gel reaction was carried out in a sealed crystallization dish (diameter 90 mm) at 65°C for 12 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material precursor.

[0058] The composite material precursor was dried at 100°C under normal pressure for 12 hours to obtain a dry gel; the dry gel was carbonized in a high-purity nitrogen atmosphere, the temperature was increased from room temperature to 1000°C at a rate of 3°C / min, and the dry gel was carbonized at 1000°C for 2 hours to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material.

[0059] The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 5 is 0.14 g / cm 3 , with a specific surface area of ​​1662m 2 / g, room temperature thermal conductivity is 0.049W / m·K, compressive strength is 3.42MPa, and compression modulus is 5.7MPa.

[0060] Comparative Example 1 Phenol, anhydrous ethanol and hydrochloric acid (hydrogen chloride concentration is 1 mol / L) are stirred at 30°C and 300 rpm for 10 minutes to obtain a uniform mixed solution; the mixed solution and formaldehyde are mixed and stirred at 50°C and 300 rpm for 15 minutes to obtain a uniform prepolymer solution; wherein the molar ratio of hydrogen chloride to anhydrous ethanol in phenol, formaldehyde and hydrochloric acid is 1:2.0:3.6:43.

[0061] The uniform prepolymerized solution was placed in a sealed crystallization dish (90 mm in diameter) at 60° C. to carry out a sol-gel reaction for 12 hours to obtain a phenolic aerogel material precursor.

[0062] The phenolic aerogel material precursor is dried at 100°C under normal pressure for 12 hours to obtain a dry gel; the dry gel is carbonized in a high-purity nitrogen atmosphere, the temperature is increased from room temperature to 800°C at a rate of 5°C / min, and the carbonization reaction is carried out at 800°C for 2 hours to obtain a carbon aerogel material.

[0063] The density of the carbon aerogel material prepared in Comparative Example 1 is 0.083 g / cm 3 , with a specific surface area of ​​912m 2 / g, the thermal conductivity at room temperature is 0.063W / m·K, the thermal conductivity at 1500℃ is 0.092W / m·K, the compressive strength is 0.06MPa, and the compression modulus is 0.10MPa.

[0064] It can be seen from Examples 1 to 5 and Comparative Example 1 that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material of the present invention has low thermal conductivity, high specific surface area, high compressive strength and compression modulus, and the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material of the present invention has excellent mechanical properties and thermal insulation properties.

[0065] The performance of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 was tested. The nitrogen adsorption test graph of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the adsorption curve is a typical IV type adsorption isotherm, indicating that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material has rich mesopore and micropore structure; the SEM image of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 has a hollow carbon fiber structure and a rich pore structure; the X-ray diffraction spectrum of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is as follows Figure 3 As shown by Figure 3It can be seen that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 has an obvious carbon diffraction peak between 20 and 30 degrees; the Raman spectrum of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is as follows: Figure 4 As shown by Figure 4 It can be seen that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 has a -1 and 1600cm -1 There is a clear sp nearby 2 With sp 3 Hybridized carbon type, I D / I G <1, having a higher degree of graphitization; The compressive stress-strain curve of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 is as shown in Figure 5 As shown by Figure 5 It can be seen that the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared in Example 1 has good compression resistance.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material, characterized in that: The following steps are included: 1) Mixing phenol monomer, aldehyde monomer, alcohol solvent and acid catalyst to obtain a prepolymerization solution; 2) impregnating polyacrylonitrile-itaconic acid fiber felt in a prepolymerization solution at normal pressure and then performing a sol-gel reaction to obtain a composite material precursor; 3) drying and carbonizing the composite material precursor in sequence at normal pressure to obtain a polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material; The acidic catalyst comprises one or more of hydrochloric acid, salicylic acid, m-hydroxybenzoic acid and gallic acid.

2. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 1, characterized in that: Step 1) The molar ratio of the phenol monomer, the aldehyde monomer, the acidic catalyst and the alcohol solvent is 1:2.0-2.5:3.6-5.0:40-45.

3. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 1 or 2, characterized in that: The phenolic monomers include one or more of phenol, resorcinol, aminophenol, butylphenol and bisphenol A; the aldehyde monomers include one or more of formaldehyde, glutaraldehyde, paraformaldehyde and furfural; the alcohol solvents include one or more of anhydrous ethanol, n-propanol, isopropanol and n-butanol.

4. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 3, characterized in that: Step 1) The mixing speed is 300-450 rpm, and the mixing temperature is 30-50°C.

5. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 3, characterized in that: The polyacrylonitrile-itaconic acid fiber felt is prepared by the following steps: acrylonitrile, itaconic acid, an initiator and a solvent are polymerized to obtain an acrylonitrile copolymer, and the acrylonitrile copolymer is sequentially subjected to dry-jet wet spinning and needle punching to obtain the polyacrylonitrile-itaconic acid fiber felt; the mass ratio of acrylonitrile to itaconic acid is 97-99:

2.

6. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 1, characterized in that: Step 2) The temperature of the sol-gel reaction is 60-70° C., and the time of the sol-gel reaction is 11-13 hours.

7. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 6, characterized in that: Step 3) The temperature of the atmospheric pressure drying is 90-120° C., and the time of the atmospheric pressure drying is 10-18 hours.

8. The method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 1 or 6, characterized in that: Step 3) The temperature of the carbonization reaction is 800-1400°C, the time of the carbonization reaction is 2h, and the heating rate from room temperature to the carbonization reaction temperature is 3-5°C / min; the carbonization reaction is carried out under a nitrogen atmosphere.

9. The polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material prepared by the method for preparing the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to any one of claims 1 to 8, characterized in that: The density of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material is 0.13-0.16 g / cm 3 , the specific surface area is 1662~1942m 2 / g, thermal conductivity at room temperature is 0.017~0.049W / m·K , The compression strength is 2.17~4.03MPa.

10. The use of the polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material according to claim 9, characterized in that: The polyacrylonitrile-itaconic acid fiber felt reinforced carbon aerogel composite material is used in thermal insulation, adsorption and electromagnetic shielding.

Citation Information

Patent Citations

  • Carbon aerogel with high specific surface area and preparation method thereof

    CN115504451A

  • A method for preparing ablation-resistant heat-insulating carbon aerogel composite material

    CN118637937B

  • Fiber-reinforced phenolic aldehyde-based carbon aerogel composite material and preparation method thereof

    CN118954482A

  • Method for preparing carbon fiber precursor by two-step process of aqueous suspension and solution polymerization

    CN102517671A

  • Middle-modulus high-strength polyacrylonitrile-based carbon fiber, and preparation method thereof

    CN102766989A